2021
DOI: 10.1002/adhm.202100146
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Engineering for Mimics and Modulations of Immune Functions

Abstract: In the field of regenerative medicine, advances in tissue engineering have surpassed the reconstruction of individual tissues or organs and begun to work towards engineering systemic factors such as immune objects and functions. The immune system plays a crucial role in protecting and regulating systemic functions in the human body. Engineered immune tissues and organs have shown potential in recovering dysfunctions and aplasia of the immune system and the evasion from immune‐mediated inflammatory responses an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 154 publications
(171 reference statements)
0
1
0
Order By: Relevance
“…In recent years, regenerative medicine has emerged as an alternative approach to tissue and organ repair, and tissue engineering has emerged as a cross-disciplinary field with great potential for growth. Studies have shown that the combination of immunomodulation and tissue engineering lays the foundation for new therapies that contribute to tissue and organ recovery and regeneration ( 101 ). The immune system protects tissues and organs, guiding tissue repair, inducing tolerance and regulating autoimmunity ( 102 ).…”
Section: Ivdd Immunomodulatory Therapiesmentioning
confidence: 99%
“…In recent years, regenerative medicine has emerged as an alternative approach to tissue and organ repair, and tissue engineering has emerged as a cross-disciplinary field with great potential for growth. Studies have shown that the combination of immunomodulation and tissue engineering lays the foundation for new therapies that contribute to tissue and organ recovery and regeneration ( 101 ). The immune system protects tissues and organs, guiding tissue repair, inducing tolerance and regulating autoimmunity ( 102 ).…”
Section: Ivdd Immunomodulatory Therapiesmentioning
confidence: 99%